PROGRAM GERAKAN LITERASI MA’ARIF DALAM MENINGKATKAN MODERASI BERAGAMA (WASATIYYAH ISLAM) - Hamidulloh Ibda; Aji Sofanudin (Tatar Pasundan : Jurnal Diklat Keagamaan, 2021)
The purpose of this study is to describe religious moderation in Ma'arif Literacy Movement  program, Nahdlatul Ulama Central Java in the period 2018-2023. This research method is descriptive qualitative by using the techniques of observation, documentation, and interviews to collect the data. The results show that religious moderation through Ma'arif Literacy Movement  program was very effective in forming literate and moderate characters. The religious moderation characted instilled in Ma'arif Literacy Movement comes from Strengthening Character Education, basic principles of Aswaja Annahdliyah, Ukhuwah Nahdliyah, and Mabadi Khaira Ummah. The impact of the program makes teachers and students literate and moderate.Keywords: Religious Moderation; GLM, Literacy; Ma'arif; Students